2022
DOI: 10.3390/ma15145057
|View full text |Cite
|
Sign up to set email alerts
|

Boosting of Magnetic, Ferroelectric, Energy Storage Efficiency, and Piezoelectric Properties of Zn Intercalated SrBi4Ti4O15-Based Ceramics

Abstract: An appropriate amount of Zn-ions are incorporated into the high Curie temperature bismuth layer-structure ferroelectric material to fabricate Sr0.2Na0.4Pr0.4Bi4Ti4O15:xwt%ZnO; (SNPBT:xZn), with x = 0, 0.10, 0.15, and 0.20 ceramic series to investigate the magnetic, ferroelectric, and energy storage efficiency and piezoelectric properties. Pure SNPBT and SNPBT:xZn ceramics have maintained their structure even after the intercalation of Zn-ions at the lattice sites of SNPBT. The addition of ZnO in SNPBT has impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Moreover, during the high-temperature sintering process of the ceramics, the highly voltaic nature of Bi was unavoidable, which resulted in the appearance of vacancies. Hence, for a charge-neutrality situation, oxygen ions started to evaporate as well, and these vacancies can be overcome by the intercalation of Mn ions to reduce the mobility defect and increment of ferroelectric properties [ 38 ]. Afterwards, for CBTNF:0.20Mn, the value of P S ~14.7 µC/cm 2 started to decrease ( Figure 5 b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, during the high-temperature sintering process of the ceramics, the highly voltaic nature of Bi was unavoidable, which resulted in the appearance of vacancies. Hence, for a charge-neutrality situation, oxygen ions started to evaporate as well, and these vacancies can be overcome by the intercalation of Mn ions to reduce the mobility defect and increment of ferroelectric properties [ 38 ]. Afterwards, for CBTNF:0.20Mn, the value of P S ~14.7 µC/cm 2 started to decrease ( Figure 5 b).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon is called back-switching at the diffusion temperature. The addition of Mn ions due to its multi-valence nature is capable of occupying the unbound misfits, which results in the development of electronic-charge dispersal at the grain boundaries, which reduce back-switching occurrence even at high-temperature annealing [ 38 ]. Herein, it can be observed that for CBTNF:0.20Mn ceramic, the d 33 value decreased to 25.2 pC/N (at room temperature) as the solubility limit of the Mn ions at vacant A and B sites in the CBTNF counterpart attained its maximum limit (percolation threshold).…”
Section: Resultsmentioning
confidence: 99%